Banff 2013 Meeting Report: Inclusion of C4d‐Negative Antibody‐Mediated Rejection and Antibody‐Associated Arterial Lesions. Issue 2 (February 2014) - Haas, M.; Sis, B.; Racusen, L. C.; Solez, K.; Glotz, D.; Colvin, R. B.; Castro, M. C. R.; David, D. S. R.; David‐Neto, E.; Bagnasco, S. M.; Cendales, L. C.; Cornell, L. D.; et al.
<x xml:space="preserve">Abstract</x> The 12th Banff Conference on Allograft Pathology was held in Comandatuba, Brazil, from August 19–23, 2013, and was preceded by a 2‐day Latin American Symposium on Transplant Immunobiology and Immunopathology. The meeting was highlighted by the presentation of the findings of several working groups formed at the 2009 and 2011 Banff meetings to: (1) establish consensus criteria for diagnosing antibody‐mediated rejection (ABMR) in the presence and absence of detectable C4d deposition; (2) develop consensus definitions and thresholds for glomerulitis (g score) and chronic glomerulopathy (cg score), associated with improved inter‐observer agreement and correlation with clinical, molecular and serological data; (3) determine whether isolated lesions of intimal arteritis ("isolated v") represent acute rejection similar to intimal arteritis in the presence of tubulointerstitial inflammation; (4) compare different methodologies for evaluating interstitial fibrosis and for performing/evaluating implantation biopsies of renal allografts with regard to reproducibility and prediction of subsequent graft function; and (5) define clinically and prognostically significant morphologic criteria for subclassifying polyoma virus nephropathy. The key outcome of the 2013 conference is defining criteria for diagnosis of C4d‐negative ABMR and respective modification of the Banff classification. In addition, three new Banff Working Groups were initiated.